Towards an integrated understanding of awe: Exploring subjective, behavioral, and physiological measurements - Takano, Ryota (Emotion Studies, 2024)
Awe is an emotional response that has long been examined in the humanities and sociology as a sublime phenomenon, and has recently attracted attention in psychology. While previous studies investigated the emotion of awe with different methodologies and approaches, the current empirical literature still lacks an integrated perspective. This paper reviews and compares studies on awe using subjective, behavioral and physiological/neural measures, and subsequently proposes an overarching framework to understand awe through the lens of functions of awe. I further discussed how we could establish an interdisciplinary basis for understanding awe and integrate diverse methodological approaches.